2015
DOI: 10.1111/eci.12420
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and urinary microRNA profile in focal segmental glomerulosclerosis: a pilot study

Abstract: Background MicroRNAs (miRNAs) are non-coding RNA molecules that play important roles in the pathogenesis of various kidney diseases. We investigated whether patients with minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS) have distinct circulating and urinary miRNA expression profiles that could lead to potential development of noninvasive biomarkers of the disease. Materials and methods Exosome miRNAs were extracted from plasma and urine samples of patients with primary FSGS (n=16) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…reported that miR-29c levels in UExos correlated with the chronicity and glomerular sclerosis in human patients with lupus nephritis11. Furthermore, miR-1915 and miR-663 levels in UExo were downregulated in patients with focal segmental glomerulosclerosis compared to healthy controls, whereas those of miR-155 were upregulated in these patients12. We also reported altered levels of miR-26a and miR-146a in the urine of CKD model mice23.…”
supporting
confidence: 54%
“…reported that miR-29c levels in UExos correlated with the chronicity and glomerular sclerosis in human patients with lupus nephritis11. Furthermore, miR-1915 and miR-663 levels in UExo were downregulated in patients with focal segmental glomerulosclerosis compared to healthy controls, whereas those of miR-155 were upregulated in these patients12. We also reported altered levels of miR-26a and miR-146a in the urine of CKD model mice23.…”
supporting
confidence: 54%
“…miR-342-3p had been found to be upregulated in prion disease [27], cancer colon [28], irritable bowel disease [29] obesity [30], T1DM and T2DM [24]. In like manar, plasma levels of miR-30b, miR-30c and miR-342 were up regulated in patients with minimal change disease compared to patients with focal Segmental Glomerulosclerosis(FGSC) and controls [31]. In another study, the expression of miR-342-3p was significantly decreased in systemic lupus erythromatous patients with active nephritis and all of the signature miRNA ƀ342 target genes are in the transforming growth factor b signaling pathways [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The association between miR-2861, miR-1915-3p, and miR-4532 followed a near doseā€“response relationship with IFTA highlighted by the lower urinary levels per increasing grade of IFTA, and may suggest a role for fibrosis formation in DN. Previous studies reported the up-regulation of miR-2861 and miR-1915-3p in patients with type 2 diabetes with microalbuminuria (31) and down-regulation of miR-1915-3p in focal segmental glomerulosclerosis patients (34). However, these miRNAs were assessed in urinary exosomes; very few patients were enrolled in these studies (n < 20), and none of them had biopsy-proven DN.…”
Section: Discussionmentioning
confidence: 99%